2015
DOI: 10.1021/acs.jpca.5b03555
|View full text |Cite
|
Sign up to set email alerts
|

Hydration, Orientation, and Conformation of Methylglyoxal at the Air–Water Interface

Abstract: Aqueous-phase processing of methylglyoxal (MG) has been suggested to constitute an important source of secondary organic aerosol (SOA). The uptake of MG to aqueous particles is higher than expected because its carbonyl moieties can hydrate to form geminal diols, as well as because MG and its hydration products can undergo aldol condensation reactions to form larger oligomers in solution. MG is known to be surface active, but an improved description of its surface behavior is crucial to understanding MG-SOA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(74 citation statements)
references
References 81 publications
3
71
0
Order By: Relevance
“…23,41,44,49,61,70,71,73,79,80,92,94 More recent efforts have focused on gaining molecular-level insights into complex interfaces by determining specific hydrogen-bonding patterns, surface propensity and binding motifs of dissolved species, and effects of interfacial electric fields. 15,33,38,65,66,72,91,99,107 These studies demonstrated that interfacial water molecules reorient to point their hydrogen atoms toward negatively charged surfaces and away from positively charged surfaces. 73 Zwitterionic headgroups of phospholipid monolayers on aqueous subphases reorient water molecules to a lesser extent, but along the same direction as negatively charged headgroups.…”
Section: Introductionmentioning
confidence: 92%
“…23,41,44,49,61,70,71,73,79,80,92,94 More recent efforts have focused on gaining molecular-level insights into complex interfaces by determining specific hydrogen-bonding patterns, surface propensity and binding motifs of dissolved species, and effects of interfacial electric fields. 15,33,38,65,66,72,91,99,107 These studies demonstrated that interfacial water molecules reorient to point their hydrogen atoms toward negatively charged surfaces and away from positively charged surfaces. 73 Zwitterionic headgroups of phospholipid monolayers on aqueous subphases reorient water molecules to a lesser extent, but along the same direction as negatively charged headgroups.…”
Section: Introductionmentioning
confidence: 92%
“…[25][26][27][28][29][30][31][32][33][34][35][36] More recent efforts have focused on gaining molecular-level insights into complex interfaces by determining specific hydrogen bonding patterns, surface propensity and binding motifs of dissolved species, and effects of interfacial electric fields. [37][38][39][40][41][42][43][44][45] These studies demonstrated that interfacial water molecules reorient to point their hydrogen atoms toward negatively charged surfaces and away from positively charged surfaces. 29 Zwitterionic headgroups of phospholipid monolayers on aqueous subphases reorient water molecules to a lesser extent, but along the same direction as negatively charged headgroups.…”
Section: Introductionmentioning
confidence: 92%
“…SFG signals recorded with different polarization combinations for the SFG, visible and infrared fields further contain the orientational information of interfacial molecular groups, accessible through their vibrations. [7][8][9][10][11][12][13][14][15][16][17] For example, Shen and Wang groups explored the orientation of the free O-H groups of the interfacial water molecules. [8][9][10][11]18,19 Tyrode, Johnson, and co-workers investigated the molecular orientation of several organic molecules at the air-water interface.…”
Section: Introductionmentioning
confidence: 99%